GEOPOLYMER CONCRETE USING FLY ASH, TRASS, SIDOARJO MUD BASED MATERIAL - Januarti Jaya Ekaputri; Triwulan Triwulan (Institut Teknologi Sepuluh Nopember, 2011)
This paper presents the results of investigation to assess the mechanical properties of geopolymer concrete made with fly ash as a base material. Previous study showed that the compressive strength of geopolymer concrete were dependent on pozzolanic materials used and the concentration of activator solution in the mixture. The effort to use Sidoarjo Mud and trass as an additive material in the mixture was investigated in this study to analyze the mechanical properties of the concrete. NaOH solution mixed with Na2SiO3 was used as the activator solution which varied from 8 M to 14 M. Ratio of Na2SiO3 to NaOH solution by mass were also varied from 0.5 to 2.5 Trass and Sidoarjo Mud were introduced as the filler and mixed with fly ash to replace the volume of fly ash. Compressive strength test of cylindrical specimens at 28 days, split strength test and porosity test were carried out comprehensively to compare the specimens from each composition. The results showed that the best concrete will be produced when denser NaOH solution was used. Ratio of Na2SiO3 to NaOH in the solution also plays an important role to improve the mechanical properties of concrete. The result of this study also shows that Sidoarjo Mud is a prospective material for making geopolymer concrete.